Effect of vitamin Dȝ on antiphospholipid antibodies in hospitalized patients with moderate to severe COVID-19 - Sales, Lucas Peixoto (2024)
Objective: To investigate the effect of a single oral dose of 200,000 IU of vitamin Dȝ on antiphospholipid antibodies in hospitalized patients with moderate to severe COVID-19. Methods: This is a post-hoc, exploratory analysis from a double-blind, placebo-controlled, randomized clinical trial performed in two centers in São Paulo, Brazil. Hospitalized patients with COVID-19 were randomly assigned to receive either vitamin Dȝ (n = 97) or placebo (n = 97). In this post-hoc analysis, the endpoints were titers and frequency of anti−β2-Glycoprotein-I (aβ2-GP) and Anticardiolipin (aCL) antibodies [Immunoglobulin G, M and A (IgG, IgM and IgA)]. Results: Overall mean (SD) age was 55.3 (13.9) years, Body Mass Index (BMI) was 32.2 (7.1 kg/m2 ), and 106 participants (54.6%) were male. There was a significant group by time interaction (p = 0.046) for frequency of aCL IgG, with increased values from baseline to discharge in the placebo group [n (%), from 13 (13.4) to 25 (25.8)] compared to the vitamin Dȝ [from 25 (25.8) to 29 (29.9)]. However, the frequency of aCL IgG did not change between the groups on discharge. No significant differences between vitamin Dȝ and placebo groups were found for any other autoantibodies. Conclusion: These findings do not support the use of a single oral dose of 200,000 IU of vitamin Dȝ to modulate autoantibodies in hospitalized patients with moderate to severe COVID-19.